Handel, his contemporaries and early English oratorio - Gardner, Matthew (Muzikološki zbornik, 2012)
Surveys the development of English oratorio from the first public performances of Handel's Esther (1732) until c. 1740. Handel's influence over his English contemporaries is discussed referring to style, formal design, subject choice and allegorical content, providing a more complete than hitherto picture of the genre in the 1730s.
Keywords: angleški oratorij; Boyce, William, 1711-1779; English oratorio; Green, Maurice, 1696-1755; Händel, Georg Friedrich, 1685-1759; Händel: Esther